The Prospects of Sustainable Desert Agriculture to Improve Food Security in Oman - Mbaga, Msafiri Daudi (Consilience, 2015)
Food security will continue to be one of the important issues occupying policy makers in the Middle East and Oman in particular. Desert countries such as Oman depend significantly on imported food commodities for food security because the desert environment is harsh in such a way that only very little food can be produced locally. As a result, Oman produces only a fraction of the food it consumes, and most of the food, especially grains and red meat is imported. Land and water scarcity are among the leading constraints to agricultural production such that by 2050, Oman is expected to depend solely on imports to meet food security needs. This paper proposes alternative technologies and approaches that can be employed by Oman under desert agriculture to help improve domestic food production and thus food security in the country.